1993
DOI: 10.1161/01.str.24.6.809
|View full text |Cite
|
Sign up to set email alerts
|

Amount of blood on computed tomography as an independent predictor after aneurysm rupture.

Abstract: After admission to the hospital of patients with aneurysmal subarachnoid hemorrhage, we assessed the predictive value of the extent of the hemorrhage on computed tomography in addition to that of clinical grading scales for poor outcome, infarction, and rebleeding. We studied 471 consecutive patients with aneurysmal subarachnoid hemorrhage and used logistic regression with step-wise forward selection of variables. On admission, poor outcome was predicted by a low Glasgow Coma Scale score (o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
75
3
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(87 citation statements)
references
References 28 publications
7
75
3
2
Order By: Relevance
“…2 It occurs in approximately one third of patients, mostly between the fourth and the tenth days after the hemorrhage. 3,4 Independent predictors for DCI are the neurological condition on admission and the amount of extravasated blood on the initial CT. [5][6][7] In a recent study, we also found that cerebral perfusion on the admission CT is a strong predictor for the development of DCI. 8 Because it is plausible that acute hydrocephalus has a negative influence on the cerebral perfusion, hydrocephalus on the admission scan may be a risk factor for DCI as well.…”
mentioning
confidence: 71%
“…2 It occurs in approximately one third of patients, mostly between the fourth and the tenth days after the hemorrhage. 3,4 Independent predictors for DCI are the neurological condition on admission and the amount of extravasated blood on the initial CT. [5][6][7] In a recent study, we also found that cerebral perfusion on the admission CT is a strong predictor for the development of DCI. 8 Because it is plausible that acute hydrocephalus has a negative influence on the cerebral perfusion, hydrocephalus on the admission scan may be a risk factor for DCI as well.…”
mentioning
confidence: 71%
“…[3][4][5][6]9,10,[18][19][20][22][23][24][25][27][28][29][30][31]33,[35][36][37]39,41 Ten studies were excluded because they did not evaluate aneurysm diameter as a risk factor for rehemorrhage rate. 4,6,9,18,22,24,29,36,39,41 Two other articles were excluded because one was a review and the other was an editorial. 25,36 One study was written in Japanese and was thus also excluded.…”
Section: Results Included Studiesmentioning
confidence: 99%
“…[5][6][7][8][9][10] Thick subarachnoid clot on admission CT has been associated with the development of DCI after SAH. [5][6][7][8][9][11][12][13][14][15][16][17][18][19][20] The Fisher CT grading scale, 21 which evaluates the amount of cisternal blood and the presence of intraventricular hemorrhage (IVH) or intracerebral hemorrhage (ICH), is widely used in the United States to identify patients at high risk for the development of DCI. Although the Fisher scale identifies patients with thick cisternal blood (grade 3), it does not differentiate between ICH and IVH (both grade 4), nor does it consider the potential for higher risk in patients with thick cisternal and ventricular or parenchymal blood.…”
mentioning
confidence: 99%